The cascade methods of doubly-fed induction machine for generator system - Diep-Dung Nguyen; Ngoc-Hoan Than; Duc-Tuan Hoang (Institute of Advanced Engineering and Science, 2021)
This paper presents two solutions to cascade the doubly-fed induction machines in the power generator systems. The first solution is a traditional one with the power control circuit located on the stator-side. The second solution is a new one with the power control circuit located on the rotor-side. After analysis and evaluation, it is shown that the solution with the power control circuit located on the rotor side has advantages over the solution with the power control circuit located on the stator-side. Therefore, the authors chose the solution which is a power control circuit located on the rotor side to study, analyze in-depth and run the simulation. The results show that the proposed solution has a very good quality, the output voltage of the generator always follows the grid-voltage even when changing the gird-voltage or changing the speed of the generator.